MicroRNA‐125a suppresses cell migration, invasion, and regulates hyaluronic acid synthase 1 expression by targeting signal transducers and activators of transcription 3 in renal cell carcinoma cells. Issue 2 (6th September 2018) - Sun, Maokun; Guo, Shuai; Yao, Jie; Xiao, Yilei; Sun, Ruili; Ma, Wenyi; Dong, Zhaogang
Abstract: Renal cell carcinoma (RCC) is one of the most common cancers in urology. MicroRNA‐125a (miR‐125a) has been demonstrated to be implicated in various cancers. However, the functional role of miR‐125a in RCC remains largely unclear. This study was aimed to investigate the functional role of miR‐125a and the expression relevance of signal transducers and activators of transcription 3 (STAT3) with hyaluronic acid synthase 1 (HAS1) in RCC. We revealed that miR‐125a was downexpressed in 786‐O cells, and examined transfected efficiency. According to functional assay, overexpression of miR‐125a inhibited cell migration and cell invasion, but no obvious effect was observed on cell proliferation. The luciferase activity assay showed that miR‐125a could directly target STAT3 3′‐untranslated regions. Meanwhile, quantitative polymerase chain reaction (qPCR) assay and Western blot analysis demonstrated that miR‐125a could inhibit STAT3 expression at both messenger RNA and protein levels. Furthermore, the combination sites between STAT3 and HAS1 were predicted by prediction of transcription factor binding sites database analysis. The expression of STAT3 was correlated with HAS1 expression, exemplified by the same tendency detected by qPCR assay. Taken together, our results preliminarily demonstrate that miR‐125a could constrain cell migration, invasion, and regulate HAS1 expression in RCC cells by targeting STAT3. It is likely to facilitate a better understanding of the regulation mechanisms of miR‐125a in RCC. Abstract : We report the possibility of miR‐125a controlling HAS1 expression in renal cell carcinoma progression by targeting STAT3.